Geoquímica de Rochas Metabasálticas da Mina da Palma, Bloco São Gabriel, Escudo Sul-rio-grandense: Um Possível Platô Oceânico - LOPES, ANGELA PACHECO; HARTMANN, LÉO AFRANEO (Pesquisas em Geociências, 2003)
<!-- .p { text-align: justify; } --> The Mina da Palma oceanic plateau is described for the first time in the São Gabriel Block, southern Brazilian Shield. It is composed mostly of metabasalts, marbles and metachert. Two deformational events are recognized in the Palma region, thrust faulting followed by dextral subvertical shearing. The rocks were metamorphosed in the greenschist facies, as shown by the dominant mineral assemblage albite-actinolite-chlorite-epidote-opaques. Metamorphic alteration was intense, because only a few relicts of the original magmatic textures are preserved, such as flow structure of amphibole and plagioclase. In spite of intense alteration during metamorphism, geochemical studies show that the chemical composition of many basalts is still preserved. The metabasalts are transitional tholeiite/alkaline and reflect intraplate conditions of formation. The tectonic environment was identified by field relations, such as predominance of basalts and small volume of marble and chert and minor clastic sedimentary rocks. The tectonic environment of formation is reflected in the geochemistry, particularly in multi-element spidergrams, because no significant Nb anomaly is observed in the least altered samples.Previous investigations showed the presence of an island-arc basaltic-andesitic association in the Palma region, which indicated that the geological unit contains one oceanic association and one active plate margin association. This is possibly the first description of remnants of an oceanic plateau in the Brazilian Shield.